2013
DOI: 10.1021/bm4011062
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose Stem Cells Cell Sheet Constructs Impact Epidermal Morphogenesis in Full-Thickness Excisional Wounds

Abstract: Among the wide range of strategies to target skin repair/regeneration, tissue engineering (TE) with stem cells at the forefront, remains as the most promising route. Cell sheet (CS) engineering is herein proposed, taking advantage of particular cell-cell and cell-extracellular matrix (ECM) interactions and subsequent cellular milieu, to create 3D TE constructs to promote full-thickness skin wound regeneration. Human adipose derived stem cells (hASCs) CS were obtained within five days using both thermoresponsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 56 publications
2
72
0
Order By: Relevance
“…Lin et al (31) and McLaughlin and Marra (32) reported that transplantation of human ASC sheets with fibrin-coated membranes accelerates wound healing in a 12-mm-diameter full-thickness skin defect on the backs of 6-week-old athymic nude mice. Cerqueira et al (33) reported that human ASC sheet transplantation promotes wound regeneration in 10-mm-diameter fullthickness skin defects on the backs of 5-week-old normal mice. In contrast to previous studies, the current study created a wider full-thickness skin defect with exposed bone (wound area 15 mm 2 ) on the parietal region of 16-week-old ZDF rats.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al (31) and McLaughlin and Marra (32) reported that transplantation of human ASC sheets with fibrin-coated membranes accelerates wound healing in a 12-mm-diameter full-thickness skin defect on the backs of 6-week-old athymic nude mice. Cerqueira et al (33) reported that human ASC sheet transplantation promotes wound regeneration in 10-mm-diameter fullthickness skin defects on the backs of 5-week-old normal mice. In contrast to previous studies, the current study created a wider full-thickness skin defect with exposed bone (wound area 15 mm 2 ) on the parietal region of 16-week-old ZDF rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that there are some differences in the wound healing process in rodent and human skin. The main reason of wound contraction that normally happens in rodent skin is basically due to the existence of a layer situated directly below the skin (paniculosus carnosus layer), while the healing in humans only occurs via re-epithelization and granulation tissue formation [52]. Therefore, in our study, the wound model was created by harvesting full-thickness skin and superficial fascia, in order to prevent wound contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the different number of works using stem cells either injected at the wound borders 15,36 or randomly incorporated within biomaterial-based matrices, [37][38][39][40][41][42] there is skepticism regarding the need for 3D organization. Nonetheless, this discrepancy can be correlated with the limitations of MSC differentiation toward epithelial and endothelial lineages, 43 as well as to the deficient purity/stability of epidermal stem cells cultures.…”
Section: Building Blocksmentioning
confidence: 99%
“…43 Stem cells from distinct sources, including MSCs, have shown a strong effect in HF formation. 37,39,44,45 In our recently published work, 37 the enhanced HF formation appears to be associated with keratinocyte growth factor (KGF) overexpression resulting from a direct interaction between resident keratinocytes (KCs) and transplanted hASCs cell sheet constructs. MSCs mechanisms that improve HF formation are, however, still elusive.…”
Section: Building Blocksmentioning
confidence: 99%